Features of Transport in Ultrathin Gold Nanowire Structures. Issue 6 (1st November 2012) - Pud, Sergii; Kisner, Alexandre; Heggen, Marc; Belaineh, Dagmawi; Temirov, Ruslan; Simon, Ulrich; Offenhäusser, Andreas; Mourzina, Yulia; Vitusevich, Svetlana
Abstract The origin of the interface formation appearing due to the realization of contacts to ultrathin gold nanowire devices is revealed. Such interfaces play an important role in transport mechanisms in nanowire structures and can determine the electrical and operating parameters of a nanodevice. Based on experimental results, the specific electrical properties of bundles of ultrathin gold nanowires fabricated by wet chemical synthesis and subsequently assembled and contacted with gold electrodes are reported. It is demonstrated that these properties are strongly affected by the monolayers of organic molecules inevitably present on the surface of the nanowires due to synthetic conditions. In particular, such layers form a potential barrier to tunneling of the electrons from contacts to the nanowires. The electric transport behavior of the investigated nanowire structures in the temperature range from 500 mK to 300 K obeys the model of thermal fluctuation‐induced tunneling conduction through the nanowire‐metal electrode molecular junction. Application of this model allows calculation of the parameters of the molecular potential barrier. The formation of such a molecular barrier is verified by scanning tunneling microscope (STM) and transmission electron microscope (TEM) measurements performed using a supporting graphene layer. These findings are important for designing novel nanodevices for molecular electronics on the basis of ultrathin nanowires.